The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5114/pm.2014.43817
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metformin on apoptosis induction in ovarian cancer cells

Abstract: IntroductionOvarian cancer is one of the most difficult problems in gynecologic oncology and the search for new drugs effective in the treatment of this kind of cancer, especially in cases resistant to current forms of therapy, remains a challenging priority.The aim of the studyThe aim of the study was to analyze the effect of metformin on apoptosis and the BIRC5 gene expression in ovarian cancer cell line SKOV-3. The BIRC5 gene encodes survivin protein.Material and methodsSKOV-3 cells were treated with metfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…EGFR expression with a greater capacity to invade than OVCAR-3. Rogalska et al [15] and Faramarzi et al [16] both demonstrated that the IC50 of MTF when treating SKOV-3 cells was 14mM and 14.92mM respectively, similar to our data. Another study by Huo et al [17] also showed that MTF (0-20mM) had an inhibitory effect on the proliferation of SKOV-3 cells Our study marks a significant contribution as the first to reveal the impact of combining MTF and SIM on the proliferation and viability of ovarian cancer cells.…”
Section: Plos Onesupporting
confidence: 91%
“…EGFR expression with a greater capacity to invade than OVCAR-3. Rogalska et al [15] and Faramarzi et al [16] both demonstrated that the IC50 of MTF when treating SKOV-3 cells was 14mM and 14.92mM respectively, similar to our data. Another study by Huo et al [17] also showed that MTF (0-20mM) had an inhibitory effect on the proliferation of SKOV-3 cells Our study marks a significant contribution as the first to reveal the impact of combining MTF and SIM on the proliferation and viability of ovarian cancer cells.…”
Section: Plos Onesupporting
confidence: 91%
“…40 P53 was reported to be required for MET-induced growth inhibition, senescence, and apoptosis in breast cancer cells. 41,42 In addition, Liu et al 43 reported that DOX caused early activation of P53 in tumor cells that was followed by caspase-3 activation and DNA fragmentation. DOX was reported to induce apoptosis in human colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Rogalska et al showed that MET can induce apoptosis in an AMPK-independent manner and arrest cell cycle in the S and G2/M stages in OVCAR-3 and OVCAR-4 cell lines. In OVCAR-3 and OVCAR-4 cells, apoptosis was induced through activating caspase 3/7, up-regulating Bax and Bad, and downregulating bcl-2 and bcl-xL [49]. Moreover, it was found that alteration in the BIRC5 mRNA expression was related to apoptosis induction in SKOV-3 ovarian cancer cells treated with MET.…”
Section: Gene Expression Analysismentioning
confidence: 97%